Smart Home with Voice Control Lights Using Arduino Uno R3 - Mamahit, Calvin; Wauran, Alfrets; Manoppo, Franky; Seke, Fransiskus; Ticoh, Janne (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
The development of science and technology has positively impacted human life which has now reached the age of electric voice commands An intelligent home management system allows humans to operate their house s electrical gadgets such as lighting using simple voice commands eliminating the need to move around to switch on or off equipment When users of indoor lighting use sound waves to operate the system or turn on the lights the sound sensor sends an input signal to the microcontroller which is then processed with the microcontroller s output in the form of a voltage to turn on the load The system will function when the FC 04 sound sensor receives sound input sound code The FC 04 sound sensor can only provide a digital output signal with a value of 1 and 0 in the form of a clap which is then accumulated on Arduino with a value above 400 million by the program uploaded to be used as a 5 volt output to turn on off the lights This is because when turning on the lights from a certain distance several factors can affect it including setting the sound sensor s sensitivity and noise levels in the surrounding area < p>